Knowledge Absorptive Capacity in Fintechs: Evidence From Latin America - Pimentel Bernal, Paul Marcelo (2023)
Fintechs use technologies to offer financial services in a different way than traditional ones. The Fintech sector has seen rapid growth in the global economy and has expanded access to financial services to a wide variety of users; consequently, it has drawn the attention of academics around the world. Being knowledge-intensive organisations, Fintechs can absorb knowledge as a key competence. Absorptive capacity – which includes practices to acquire, assimilate, transform, and apply knowledge - has been analysed in previous studies as a factor that can influence organisational performance. However, most studies have used data from developed countries. The objective of this ongoing study is to analyse the knowledge management (KM) practices used by a Latin American Fintech to absorb knowledge. For this, a case study with a qualitative approach will be presented, using data from an international company of Peruvian origin, specializing in leasing. Data was collected through interviews. The information collected was transcribed and categorized for analysis. The analysis will include content analysis and narrative analysis techniques, supported by Atlas.ti software. The results contribute to the KM literature in two ways: First, by describing how knowledge absorption occurs in Fintechs. Second, by systematizing evidence on how KM practices act in organisations in emerging contexts, to support absorption capacity, and consequently, contribute to organisational results. On the empirical side, this study provides specific insights to managers of companies in the financial and technological sectors in emerging contexts, on how and which practices implementing to improve KM in their organisations.